Additive effect of a single intravenous dose of acetaminophen administered at the end of laparoscopic hysterectomy on postoperative pain control with nefopam and fentanyl-based patient-controlled analgesia: a double-blind, randomized controlled trial - Seungpyo Nam; Seokha Yoo; Sun-Kyung Park; Jin-Tae Kim (BMC Anesthesiology, 2025)
Abstract Background Acetaminophen is a widely used analgesic for postoperative pain management. However, data on its combined use with nefopam for managing postoperative pain following laparoscopic hysterectomy are limited. This study evaluated the effects of a single intravenous dose of acetaminophen combined with fentanyl- and nefopam-based patient-controlled analgesia (PCA) in patients undergoing laparoscopic hysterectomy. Methods In this prospective, double-blind, randomized controlled trial, 84 patients were randomized to receive either 1 g of intravenous acetaminophen (treatment group, n = 42) or normal saline (control group, n = 42) at the end of surgery. All patients received fentanyl and nefopam via PCA, postoperatively. PCA consumption, pain scores at rest, and postoperative nausea and vomiting (PONV) scores were assessed at 1, 6, and 24 h postoperatively. Patient satisfaction and opioid-related side effects were also evaluated. The primary outcome was the total PCA consumption within the first 24 h. Results No significant difference in 24-h PCA consumption was observed between the control and treatment groups (27.9 ± 16.6 vs. 26.4 ± 11.2, P = 0.623). The pain scores at rest measured at 1, 6, and 24 h after surgery were also not significantly different between the two groups. There were no differences in the satisfaction scores, PONV scores, rescue analgesic use, adverse effects, or length of hospital stay between the groups. Conclusions A single intraoperative dose of intravenous acetaminophen, combined with nefopam- and fentanyl-based PCA, did not significantly reduce analgesic requirements, pain scores at rest, or opioid-related side effects compared with placebo in laparoscopic hysterectomy patients. Trial registration ClinicalTrials.gov (Identifier: NCT03644147 | August 21, 2018).